Quality improvement in the management of people with epilepsy and intellectual disability: the development of clinical guidance. (22nd January 2020) - Watkins, Lance; O'Dwyer, Máire; Kerr, Michael; Scheepers, Mark; Courtenay, Ken; Shankar, Rohit
ABSTRACT: Introduction : This clinical guidance looks at the specific concerns of delivery of medical treatment for people with epilepsy and intellectual disability (ID). People with ID have not been included in licensing drug trials of AEDs. However, this population has an over-representation of seizure comorbidity, treatment resistance, and polypharmacy while also being vulnerable to not having their views considered. Areas covered : This review summarizes the current most robust evidence available for the use of licensed AEDs in people with epilepsy and ID. The article provides practical evidence-based clinical information to help prescribers choose the most appropriate AED from the drugs discussed. The article highlights other important individualized factors to consider before initiating or changing antiepileptic medication. Expert opinion : A 'traffic light' coding system is applied to commonly used AEDs based on the level of evidence and expert clinical experience. Managing epilepsy in the ID population requires specialist care. Treatment plans need to be holistic and tailored to accommodate an individual's comorbidities, concurrent medications, general health, social and environmental status. There is a need for large quality trial data to assess the most suitable AEDs on seizure control and quality of life in this population with complex needs.